RETRACTED: Study of the environmental impact of the process of recycling fibrous waste - Islamov Bakhtiyor; Mamaeva Dildora; Ulukmuradov Abror; Tashpulatov Salikh; Cherunova Irina (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 116, 00001 (2024), https://doi.org/10.1051/bioconf/202411600001